Envisioning the Role of Educators’ Technological Pedagogical and Content Knowledge and Self-Regulated Learning in an English as a Foreign Language Context - Li, Wenjie (Frontiers in Psychology, 2022)
In recent decades, more and more research has been conducted on the competencies of educators in improving the role of technology in academic activities. These competencies are based on a clear platform of technological knowledge, together with the recognized aspects of vast pedagogical knowledge and rich content knowledge. In such a modern era, the knowledge of technology, pedagogy, and content knowledge (TPACK) is quite vital in getting the educators ready to turn into qualified educators to cope with the difficulties of the 21st-century. Moreover, it is considered that self-regulation is a significant factor in English as a Foreign Language (EFL) educators’ learning and professional development. In line with the literature, nurturing and boosting self-regulated learning (SRL) capabilities assist individuals to gain complicated knowledge and manage challenging problems in the process of teaching. Consequently, this review makes an effort to inspect teachers’ TPACK growth by enhancing their SRL capabilities in the process of technology-based instruction. In a nutshell, the implications of the present review were presented together with suggestions.